How motivated are patients with type 2 diabetes to change their lifestyle? A survey among patients and healthcare professionals - Linmans, Joris J. (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2015)
• We assessed the level of motivation to change lifestyle in patients with T2DM. • Patients were not motivated to increase their lifestyle. • Many patients had a deficient physical activity level. • Patients and professionals have poor agreement for the patients’ level of motivation to change. • The motivation level should be assessed regularly in usual-care to optimize lifestyle management.